Aspartic acid derivatized hydroxylated fullerenes as drug delivery vehicles for docetaxel: an explorative study. (17th November 2018) - Thotakura, Nagarani; Sharma, Gajanand; Singh, Bhupinder; Kumar, Vipin; Raza, Kaisar
Abstract: The objective of the present study was to deliver docetaxel to cancerous cells with enhanced efficacy and safety profile, using aspartic acid linked fullerenols. This aspartic acid derivatized fullerenol conjugate linked with docetaxel was characterized by UV, FT-IR and NMR spectroscopy. Studies for particle size, PDI, zeta potential and FE-SEM were also performed. The conjugate was evaluated for release kinetics, cancer cell cytotoxicity, cellular uptake using confocal laser microscopy and also for pharmacokinetic profile. Cytotoxic studies proved that there was almost 4.3 folds decrease in IC50 with significantly enhanced cellular uptake of the nanometric conjugates. It was observed that the bioavailability was enhanced by 5.8 folds when compared to that of pure DTX. The developed nanoconstructs were erythrocyte compatible and offered decreased protein binding. The findings are encouraging and offer a novel carrier with enhanced efficacy and safety of a drug, belonging to BCS class IV.